2022
DOI: 10.3390/app12042263
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Ergonomic Interventions for Improving Agricultural Work Environment: A Case Study in a Farming Organization of Korea

Abstract: Farmers are often exposed to risk factors for musculoskeletal disorders through lifting, carrying heavy loads, and sustained or repeated full-body bending. Several relevant studies on ergonomic interventions have been conducted for specific agricultural tasks, such as harvesting and pruning, by experts without involving farmers. This study introduces ergonomic interventions to mitigate risk factors in a farming organization that cultivates peaches as the main crop based on ergonomic analysis of the entire peac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…X7 (social conditions) was determined by X71 (work relations) at 0.797, X72 (work motivation) at 0.930 (the greatest), and X73 (wages) at 0.454 (the smallest). These outcomes were consistent with the research by [45], where it was concluded that job satisfaction, work environment, and work motivation significantly impact employee performance. External Factor X8 (information condition) was affected by X81 (ease of distinguishing harvested clove flowers) at 0.982 (the greatest), X82 (ease of seeing clove flowers) at 0.004, and X83 (ease of reach) at -0.079.…”
Section: Factor Analysis Test Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…X7 (social conditions) was determined by X71 (work relations) at 0.797, X72 (work motivation) at 0.930 (the greatest), and X73 (wages) at 0.454 (the smallest). These outcomes were consistent with the research by [45], where it was concluded that job satisfaction, work environment, and work motivation significantly impact employee performance. External Factor X8 (information condition) was affected by X81 (ease of distinguishing harvested clove flowers) at 0.982 (the greatest), X82 (ease of seeing clove flowers) at 0.004, and X83 (ease of reach) at -0.079.…”
Section: Factor Analysis Test Resultssupporting
confidence: 90%
“…The design of Korean melon harvesting equipment was made by taking into account the product's physical characteristics and the workers' anthropometry. It also effectively reduced postural loads and increased job satisfaction of farmers in a city in southern Korea [45]. Research [61] from 1995 to 2020 found 221 studies related to musculoskeletal disorders (MSDs) in agricultural work, which were generally reported by developed countries, and only a few countries paid attention.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the increasing prevalence of WRMSDs in the workplace, ergonomic intervention is particularly important as a preventive measure (Rostami et al, 2022). To reduce the effect of WRMSDs, several research employed administrative and engineering terms (Kee, 2022), physical and administrative interventions (Motamedzadeh et al, 2021), as well as engineering and training interventions (Esmaeili et al, 2023). These aspects are described in this review using the terms 'application of devices or tools' and 'administrative approach'.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2016), found that carrying on head was the most common practice while back loading of filled bags is practiced for heavier loads by Indian farmers. Manual activities such as lifting, carrying heavy loads involving the back, head and shoulders are associated with spinal MSDs (Benos et al, 2020) and other MSDs among farmers (Benos et al, 2020;Kee, 2022). Heavy carrying and lifting during rice crop cultivation caused MSDs among Thai rice farmers.…”
Section: Introductionmentioning
confidence: 99%